The implementation of the Environmental Agenda in Public Administration (A3P) from the perspective of the workers of the Women’s Secretariat of Pernambuco - Corcino , Kevin Ferreira; Azevedo , Gesianny Crispim de; Santos , Fernando Matheus Ferreira Tributino dos; Silva , Thales Fabrício da Costa e; Rocha , Luiza Cristina Jordão Braga Vilaça da; Valença , Marilia Nunes (Seven Editora, 2023)
Sustainable development has become evident in both the public and private sectors, requiring greater engagement from organizations and their members in policies and programs related to environmental issues. Therefore, the objective of this article is to evaluate the perception of the staff of the Women’s Secretariat of the state of Pernambuco regarding the socio-environmental actions proposed in the Environmental Agenda in Public Administration (A3P). This is a case study, with data collected through the application of a structured questionnaire to 25 public agency employees. The results indicate that the employees perceive low applicability of A3P, given the existence of specific actions that focus on the axis of proper waste management and on the axis of sustainable procurements. The research reveals that there is little communication about the existence of A3P in the Women’s Secretariat and that the lack of awareness-raising and capacity-building actions for the employees hinders the implementation of all the axes of A3P. It is concluded that adherence to A3P must be accompanied by systematic implementation, with effective awareness-raising and communication at all levels of the organization. DOI:https://doi.org/10.56238/sevened2023.006-064